A study of the heat-mediated phase transformations of praziquantel hydrates. Evaluation of their impact on the dissolution rate - Salazar Rojas, Duvernis (2022)
Fil: Fil: Salazar Rojas, Duvernis. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Área de Análisis de Medicamentos. Instituto de Química Rosario (IQUIR-CONICET); Argentina.